Cold-water immersion decreases cerebral oxygenation but improves recovery after intermittent-sprint exercise in the heat - Minett, G. M.; Duffield, R.; Billaut, F.; Cannon, J.; Portus, M. R.; Marino, F. E. (Scandinavian Journal of Medicine & Science in Sports, 2014)
This study examined the effects of post-exercise cooling on recovery of neuromuscular, physiological, and cerebral hemodynamic responses after intermittent-sprint exercise in the heat. Nine participants underwent three post-exercise recovery trials, including a control (CONT), mixed-method cooling (MIX), and cold-water immersion (10 °C; CWI). Voluntary force and activation were assessed simultaneously with cerebral oxygenation (near-infrared spectroscopy) pre- and post-exercise, post-intervention, and 1-h and 24-h post-exercise. Measures of heart rate, core temperature, skin temperature, muscle damage, and inflammation were also collected. Both cooling interventions reduced heart rate, core, and skin temperature post-intervention (P < 0.05). CWI hastened the recovery of voluntary force by 12.7 ± 11.7% (mean ± SD) and 16.3 ± 10.5% 1-h post-exercise compared to MIX and CONT, respectively (P < 0.01). Voluntary force remained elevated by 16.1 ± 20.5% 24-h post-exercise after CWI compared to CONT (P < 0.05). Central activation was increased post-intervention and 1-h post-exercise with CWI compared to CONT (P < 0.05), without differences between conditions 24-h post-exercise (P > 0.05). CWI reduced cerebral oxygenation compared to MIX and CONT post-intervention (P < 0.01). Furthermore, cooling interventions reduced cortisol 1-h post-exercise (P < 0.01), although only CWI blunted creatine kinase 24-h post-exercise compared to CONT (P < 0.05). Accordingly, improvements in neuromuscular recovery after post-exercise cooling appear to be disassociated with cerebral oxygenation, rather reflecting reductions in thermoregulatory demands to sustain force production.